Cognitive impairment after long COVID-19: current evidence and perspectives - Li, Zhitao; Zhang, Zhen; Zhang, Zhuoya; Wang, Zhiyong; Li, Hao (Frontiers in Neurology, 2023)
COVID-19 is a respiratory infectious disease caused by the SARS-CoV-2 virus. Most patients recover after treatment, but COVID-19 treatment may lead to cognitive impairment. Recent studies have found that some recoverers experience cognitive impairments such as decreased memory and attention, and sleep disorder, indicating that COVID-19 may have longerterm effects on cognitive function. Studies have found that COVID-19 may cause cognitive decline by damaging key brain regions such as the hippocampus and anterior cingulate cortex. Studies have also found that COVID-19 patients have active neuroinflammation, mitochondrial dysfunction, and microglial activation, suggesting that neuroinflammation, mitochondrial stress, and neurodegenerative changes may be potential mechanisms leading to cognitive impairment. In summary, the possibility of cognitive impairment after COVID-19 treatment deserves close attention. Large-scale follow-up studies will help further explore the impact of COVID-19 on cognitive function and provide evidence to support clinical treatment and rehabilitation practices. Neuropathological and biological studies can explore precise mechanisms in-depth and provide a theoretical basis for prevention, treatment, and intervention research. Given the risks of long-term COVID-19 and reinfection, it is necessary to integrate basic and clinical research data to maximize the maintenance of patient's cognitive function and life quality. This also provides important experience in responding to similar public health events. This article integrates clinical and basic evidence of cognitive impairment after COVID-19 and discusses potential mechanisms and future research directions.